A Rare Q-Fever Infection Diagnosed Using Metagenomic Next-Generation Sequencing in Liver Transplantation Patient: A Case Report and Literature Review - Niu X; Qiu S; Zheng Y; Li L; Tian E; Liu J; Gai W; Zhang Q; Jin H (Infection and Drug Resistance)
Xinxin Niu,1,* Shuang Qiu,1,* Yafeng Zheng,2,* Li Li,1 Eryun Tian,1 Jie Liu,1 Wei Gai,2 Qing Zhang,1 Hailong Jin1 1Department of Organ Transplantation, The Third Medical Center of Chinese PLA General Hospital, Beijing, People’s Republic of China; 2WillingMed Technology (Beijing) Co., Ltd, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing Zhang; Hailong Jin, Department of Organ Transplantation, The Third Medical Center of Chinese PLA General Hospital, Beijing, 100039, People’s Republic of China, Email zqy6920@sina.com; jhl309@sina.comAbstract: Q fever is a zoonotic disease caused by the Gram-negative bacterium Coxiella burnetii, typically transmitted through exposure to infected animal secretions. As the clinical signs of Q-fever are largely non-specific in humans, a definitive diagnosis can often be overlooked, particularly when physicians fail to consider C. burnetii on the list of differentials. This case report describes Q-fever in a male patient who had previously undergone orthotopic liver transplantation. The patient had a sudden onset of fever and received the anti-infective moxifloxacin which proved ineffective. Despite the comprehensive laboratory tests and CT imaging that were performed, the etiology remained undetermined. The patient’s blood was subjected to metagenomic next-generation sequencing (mNGS), which identified C. burnetii, after which the patient was treated with doxycycline and recovered well. Eight literature articles on Q fever infection in solid organ transplant recipients were reviewed. To our knowledge, this is the first case of Q fever identified by mNGS in an organ transplantation patient. The case underscores the potential of mNGS has in aiding the rapid detection of rare pathogens in immunocompromised patients.Keywords: Q-fever, metagenomic next-generation sequencing, case report, liver transplant, Coxiella burnetii